The importance of physiotherapeutic treatment of a patient with Moebius syndrome: Case report (Research, Society and Development, 2022)
Moebius syndrome is characterized by the presence of paralysis, usually bilateral, of the facial nerve, with possible involvement of other facial structures. The etiology is not clearly defined, MS may occur due to a vascular alteration during embryonic development that produces ischemia at the level of the cranial nerve nuclei with subsequent hypoplasia, in addition, it may be related to the use of medications, infections or agents. external, causing neurological damage in the nuclei of the cranial nerves. Surgical treatment is often essential to correct adversities arising from MS. In physical therapy treatment, a good prognosis, detailed knowledge of the clinical history, analysis of imaging exams, physical examination and inspection, sensitivity tests, and coordination are necessary. The objective of this study is to report the case of a patient with Moebius syndrome, as well as the importance of physical therapy monitoring in the treatment, prevention, improvement and maintenance of quality of life. The present study is a case report carried out in a Specialized Center for Craniofacial Anomalies, located in western Paraná, based on anamnesis, clinical and physical examination, weekly consultations and interview with the person in charge. Female patient, being followed up at the rehabilitation clinic of a State University, since she was 23 days old, and being attended at the aforementioned center in 2018. The response of the physical therapy treatment plan was positive, helping the patient to adapt and overcome their difficulties, favoring adaptations in activities of daily living, preventing possible complications, improving and maintaining muscle strength.